Tafaqquh Fid Din: Interpretasi Perti Sumbar terhadap Ayat dan Hadis Jihad dalam Upaya Pembangunan Umat - Hafizzullah; Sukri, Mhd Alfahjri; Syafriwaldi (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2024)
Abstract This research aims to describe how the interpretation of the Religious Institution of the Islamic Tarbiyah Union (PERTI) in West Sumatra about jihad, as well as to explain the institution's stance on terrorist actions carried out under the guise of jihad. A qualitative method is employed in this study, with data gathered through interviews, documentation, and literature reviews, including books, scholarly articles, religious texts, and news reports. The research is guided by Peter L. Berger's social construction theory to elucidate the construction of the religious institution PERTI in West Sumatra regarding the meaning of jihad. The findings indicate that PERTI in West Sumatra interprets jihad in verses and hadiths as a form of striving in the field of educating the community (tafaqquh fid din). This understanding of jihad is then internalized into various educational programs, ranging from elementary levels such as kindergarten and primary school to secondary school, high school, and even higher education institutions. Moreover, PERTI explicitly rejects the interpretation of jihad as warfare within the Indonesian context. The jihad undertaken by PERTI is characterized as moderate. This research contributes to enhancing the understanding of stakeholders and the general public about the diverse and moderate interpretations of jihad. It also demonstrates that religious institutions in Indonesia have their own interpretations of jihad, such as PERTI Sumatera Barat. Keywords: Meaning of Jihad, PERTI West Sumatra, Tafaqquh fid din Abstrak Penelitian ini bertujuan untuk mendeskripsikan bagaimana interpretasi lembaga Keagamaan Persatuan Tarbiyah Islamiyah (PERTI) Sumatera Barat tentang jihad, serta menjelaskan sikap lembaga keagamaan tersebut terhadap aksi teror yang mengatasnamakan jihad. Metode kualitatif digunakan dalam penelitian ini dengan data diperoleh melalui wawancara, dokumentasi, dan studi pustaka baik itu dari buku, artikel ilmiah, kitab, dan pemberitaan. Dengan mempedomani teori konstruksi sosial Peter L Berger untuk menjelaskan kontruksi lembaga keagamaan PERTI Sumbar tentang makna jihad. Hasil penelitian menunjukkan, PERTI Sumatera Barat memaknai jihad dalam ayat dan hadis dalam bentuk perjuangan dalam bidang Pendidikan umat (tafaqquh fid din). Pemahaman tentang jihad tersebut kemudian di internalisasikan ke berbagai bentuk program pendidikan yang mulai dari tingkat dasar baik TK, SD, menengah, atas bahkan perguruan tinggi. Kemudian PERTI dengan nyata menolak makna jihad dalam artian perang untuk konteks Indonesia. Jihad yang dilakukan PERTI bersifat moderat. Penelitian ini berkontribusi dalam menambah pemahaman pemangku kepentingan dan masyarakat umum dalam memahami jihad yang begitu beragam dan juga bersifat moderat. Ini juga menunjukkan bahwa lembaga keagamaan di Indonesia memiliki pemaknaan jihad sendiri seperti PERTI Sumatera Barat. Kata kunci: Makna Jihad, PERTI Sumbar, Tafaqquh fid din